PELAYANAN PUBLIK URUSAN PEMERINTAHAN DAERAH BIDANG KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKANBARU TAHUN 2014 (STUDI PENGURUSAN SURAT KETERANGAN DATANG) - Putri Lika Koertriana; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the Certificate Management Services to the Department of Population and Civil Registration (Disdukcapil) Pekanbaru. This type of research is descriptive qualitative problem solving investigated by describing the state of the subject and object of research at the present time based on factors that looked or how it is. This research was conducted at the Department of Population and Recording Sipi (Disdukcapil) which is located Pekanbaru City street Musatafa Sari No. 1, Pekanbaru. Samples are informants in this study is the Head of Population Registration and Population Movements Section Chief and the people who take care of the Certificate Coming at the Department of Population and Civil Registration (Disdukcapil) Pekanbaru. The technique of collecting data through observation, interviews and documentation. This study was conducted to investigate the implementation of public services in the manufacture of Certificate Come to identify any obstacles encountered in the implementation of the Certificate Management Service Comes at the Department of Population and Civil Registration (Disdukcapil) Pekanbaru. The formulation of the problem as follows: How the Public Service of the Regional Government Affairs of Population and Civil Registration Pekanbaru City Year 2014 (Certificate of Management Studies Coming). Results peneitian concluded that the Public Service Government Affairs Division of Population and Civil Registration of Service Certificate to the city of Pekanbaru in class pretty well, because there are indications of service is not good given servants to the public in the administration of Certificate Coming particular problem resolution time, and typing errors in the manufacture of the Certificate Coming.Keywords: Public Service, Management, Certificate Coming